Housefly larva bioconversion enhances heavy metal stabilization and antibiotic degradation during chicken manure composting - Nanyang Lu; Tinglei Zhao; Chunlai Hong; Yanlai Yao; Weijing Zhu; Leidong Hong; Tao Zhang; Hanjing Xu; Kewei Wang; Chengrong Ding; Ying Zhou; Fengxiang Zhu (Scientific Reports)
Abstract This study assessed the integration of housefly larva bioconversion with aerobic composting for chicken manure (MC) over a 45-day period (4 days of larval bioconversion + 41 days of aerobic composting) and compared it with direct composting (CK1) and sawdust-amended composting (CK2). Larval activity enhanced moisture reduction and substrate porosity, yielding 6.08% (w/w) maggot protein and reducing nutrient losses of C, N, P, and K by 13.45%, 35.08%, 62.15%, and 70.89%, respectively, relative to CK2. MC treatment accelerated humification, as evidenced by increased aromatic and humic acid content, which immobilized heavy metals, Particularly Zn and Cd via HA–metal complexation. Multivariate analyses (redundancy and CART) identified moisture (< 63 – 74%), composting duration, organic matter, and K⁺ release as principal drivers for heavy metal passivation. In the three treatmengt, degradation of tetracycline antibiotics followed the sequence OTC > CTC > DOX with MC reducing the half-life of CTC to 2.57 days through thermophilic degradation coupled with HA- and K⁺-mediated adsorption and chelation; quinolone antibiotics remained largely recalcitrant. These results demonstrate that MC composting enhances nutrient retention, heavy metal stabilization, and tetracycline removal, thereby improving the agronomic value and environmental safety of chicken manure–derived biofertilizer.